The effect of performance expectancy, effort expectancy, social influence, facilitating conditions on mobile wallet adoption - Anwar, Resa Nurlaela; Alviayatun, Tuti (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine how much influence performance expectancy, effort expectancy, social influence, facilitating conditions have on mobile wallet adoption of DANA car wallet users in Karawang City. The data collection method used was by giving questionnaires to 100 respondents using DANA at least 3 (three) times in the past month. The sample technique uses non-probability sampling and the analytical tool technique uses multiple linear regression and simple linear. The results of this study indicate that performance expectancy, effort adoption expectancy, social influence, facilitating conditions have an effect on mobile wallets. The magnitude of 0.611 where 61.1% of the variables of performance expectancy, effort expectancy, social influence and facilitating conditions can be explained, influenced by mobile wallet adoption while the remaining 0.39% is influenced by other variables outside the model. Partially, performance expectancy has an influence of 0.540 which means that it is 54.0%, effort expectancy is 0.488 which means that it is 48.8%, social influence is 0.482 which means that it is 48.2%, and facilitating conditions is 0.634 which means that by 63.4%.